CORRELATION AND PATH COEFFICIENT ANALYSIS FOR YIELD AND ITS COMPONENT TRAITS IN SUNFLOWER HYBRIDS (Helianthus annuus L.) - K. VARALAKSHMI*, S. NEELIMA and K.N. SREENIVASULU, (The Journal of Research ANGRAU, 2023)
and to assess the nature and extent of direct and indirect effects of component characters on seed yield. Tenparental lines (4 lines and 6 testers), twenty-four hybrids and four checks were evaluated during Rabi, 2018-19 in arandomized block design with two replications. A total of eighteen traits were recorded and subjected these forcorrelation and path coefficient analysis. The results indicated that seed yield had strongest positive associationwith oil yield followed by head diameter, number of seeds per head, leaf area index, seed set per cent, plant height,stem girth, 100 seed weight and number of leaves per plant. Whereas, the path coefficient analysis indicated that thetraits viz., oil yield followed by number of seeds per head and leaf area index exhibited significant positive directeffects on seed yield. In addition, the indirect effects of most of the traits were also high with seed yield via oil yield,days to 50 % flowering and number of seeds per head.